Introduction to imprecise probabilities - Augustin, Thomas (Chichester, West Sussex : John Wiley & Sons Inc., 2014)
"In recent years, the theory has become widely accepted and has been further developed, but a detailed introduction is needed in order to make the material available and accessible to a wide audience. This will be the first book providing such an introduction, covering core theory and recent developments which can be applied to many application areas. All authors of individual chapters are leading researchers on the specific topics, assuring high quality and up-to-date contents. An Introduction to Imprecise Probabilities provides a comprehensive introduction to imprecise probabilities, including theory and applications reflecting the current state if the art. Each chapter is written by experts on the respective topics, including: Sets of desirable gambles; Coherent lower (conditional) previsions; Special cases and links to literature; Decision making; Graphical models; Classification; Reliability and risk assessment; Statistical inference; Structural judgments; Aspects of implementation (including elicitation and computation); Models in finance; Game-theoretic probability; Stochastic processes (including Markov chains); Engineering applications. Essential reading for researchers in academia, research institutes and other organizations, as well as practitioners engaged in areas such as risk analysis and engineering"--
"Provides a comprehensive introduction to imprecise probabilities, including theory and applications reflecting the current state of the art"--
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Probabilities; MATHEMATICS -- Probability & Statistics -- General; Probabilities; Electronic books; Electronic books